Method for wet repair of lithium iron phosphate
Patent Information
- Application Number
- CN202610716956.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-22
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]本发明旨在解决现有的磷酸铁锂的修复方法成本高、环保性差、修复效果不佳的问题
本发明的磷酸铁锂湿法修复的方法通过有氧煅烧可去除废旧 LFP黑粉中残余的碳杂质和部分有机污染物,生成结构稳定的前驱体铁红,为后续补锂修复奠定基础;惰性气体保护下的烧结能避免修复过程中 Fe2+被二次氧化,同时促进复合添加剂与前驱体铁红的反应,实现 Li+的精准补充和晶格缺陷的修复,从根源上解决了废旧 LFP 因Li+缺失导致的物相改变和结构坍塌问题。
Smart Images

Figure FT_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium iron phosphate remediation technology, specifically to a method for wet remediation of lithium iron phosphate. Background Technology
[0002] With the rapid development of the global electric vehicle and mobile electronic device industries, lithium iron phosphate (LFP) batteries have been widely used in the power battery field due to their advantages such as high safety, long cycle life, and relatively low cost. However, during long-term charge-discharge cycles, the cathode material of lithium iron phosphate batteries experiences irreversible performance degradation: due to the Li... + The continued absence of Fe 2+ Oxidized to Fe 3+ This leads to phase changes and lattice collapse of LiFePO4, ultimately causing the battery to reach the end of its service life and be decommissioned.
[0003] If these retired and used batteries are disposed of indiscriminately, their electrolytes and organic waste will seep into the soil and water, causing serious environmental pollution. At the same time, the waste of valuable metal resources such as lithium, iron, and phosphorus will exacerbate the pressure on the supply of primary resources. Therefore, the recycling and remediation of waste lithium iron phosphate batteries has important strategic resource significance and environmental protection value.
[0004] In existing technologies, the main methods for repairing lithium iron phosphate include hydrometallurgy, high-temperature sintering, and hydrothermal methods. Among these, hydrometallurgical repair has become the mainstream due to its relatively simple operation and wide applicability. However, existing hydrometallurgical repair technologies have significant drawbacks: First, they require the use of large amounts of chemical leaching reagents and solvents, resulting in high raw material costs, and the procurement, storage, and disposal of reagents add an additional economic burden. Second, the chemical reagent reaction process generates a large amount of wastewater and solid waste, which is difficult to treat and puts significant pressure on the environment. Third, the process conditions are demanding, requiring precise control of parameters such as temperature and pH, relying on high-precision equipment, resulting in high process complexity and difficulty in large-scale promotion. Fourth, a single lithium replenishment reagent cannot simultaneously address lattice repair and performance improvement, and the specific capacity, cycle stability, and other core indicators of the repaired material are difficult to meet the requirements for reuse. Summary of the Invention
[0005] This invention aims to solve the problems of high cost, poor environmental performance, and unsatisfactory repair effects of existing lithium iron phosphate remediation methods.
[0006] To address the above problems, this invention provides a method for wet remediation of lithium iron phosphate, comprising the following steps: Step 1: After sieving the waste lithium iron phosphate (LFP) black powder, calcine it under aerobic conditions to obtain the precursor iron red. Step 2: Add the precursor iron oxide and composite additive to pure water and stir evenly to obtain a mixed slurry; Step 3: Mill the mixed slurry to obtain a nano-sized slurry; Step 4: Spray dry the nano-sized slurry to obtain powder; Step 5: Sinter the powder under inert gas protection to obtain sintered material; Step 6: Crush the sintered material to obtain repaired lithium iron phosphate.
[0007] The wet remediation method for lithium iron phosphate provided by this invention has, but is not limited to, the following beneficial effects compared to existing technologies: The lithium iron phosphate wet remediation method of this invention removes residual carbon impurities and some organic pollutants from waste LFP black powder through aerobic calcination, generating a structurally stable precursor, iron oxide red, which lays the foundation for subsequent lithium replenishment remediation; sintering under inert gas protection avoids Fe during the remediation process. 2+ It is subjected to secondary oxidation, which simultaneously promotes the reaction between the composite additive and the precursor iron oxide red, thereby achieving Li + The precise replenishment and lattice defect repair fundamentally solve the problem of waste LFP due to Li... + The problem of phase changes and structural collapse caused by missing components.
[0008] Moreover, the calcination of waste LFP black powder after sieving reduces the ineffective consumption in subsequent sand milling and reaction stages, and avoids incomplete reaction and increased waste caused by impurities. At the same time, the process does not require the addition of complex chemical leaching reagents, but only mixes pure water with composite additives, which greatly reduces the wastewater pollution caused by chemical reagents in traditional wet remediation. The sand milling nano-sizing step can increase the specific surface area of the slurry particles, so that the composite additives can have more sufficient contact with the precursor iron oxide. Subsequent spray drying granulation can form a powder with good flowability, ensuring the uniformity of reaction during sintering and avoiding local insufficient lithium replenishment or uneven structural repair.
[0009] More importantly, this process only treats waste LFP black powder, without the need for complex disassembly and leaching of the entire battery, reducing raw material loss and energy consumption; the repaired material can be directly reused as a cathode material, realizing the recycling of valuable metals such as lithium, iron, and phosphorus, alleviating dependence on primary resources, and avoiding environmental pollution caused by the random disposal of waste batteries.
[0010] Preferably, the components of the composite additive include lithium carbonate, glucose, lithium dihydrogen phosphate, titanium dioxide, and polyethylene glycol.
[0011] Specifically, lithium carbonate, as the core lithium replenisher, can precisely replenish the Li in waste LFP. + Missing; glucose has both reducing agent and granulation aid functions, and during the sintering process, it can remove any residual Fe that may remain after calcination. 3+ Reduced to Fe2+ It can also help remove residual impurities and prevent Fe 3+ The resulting electrochemical performance degradation; lithium dihydrogen phosphate can finely adjust the lithium-phosphorus ratio and further optimize the crystal structure; titanium dioxide and polyethylene glycol form a composite coating layer, which reduces the interfacial impedance of the repaired material during cycling and improves the ion conduction efficiency, thus solving the defect that traditional single lithium replenishment reagents cannot simultaneously achieve structural repair and performance improvement.
[0012] Moreover, the components of the selected composite additives are all industrial-grade, readily available, and low-cost raw materials, and there is no need to add complex chelating agents and solvents, reducing the procurement and processing costs of chemical reagents. At the same time, the composite additives do not generate any toxic or harmful byproducts during the reaction process, and the reducing effect of glucose can also reduce the emission of pollutants during sintering, further reducing environmental pressure. Each component can be uniformly dispersed or dissolved in pure water, forming a stable mixed slurry with the precursor iron oxide, avoiding the problems of easy precipitation and uneven reaction of traditional repair reagents. Furthermore, there is no antagonistic effect between the additives, and they can maintain functional stability during subsequent sand milling and sintering processes, ensuring the consistency of repair effects and batch stability.
[0013] Preferably, the mass ratio of lithium carbonate, glucose, lithium dihydrogen phosphate, titanium dioxide, and polyethylene glycol is 50:5:2:1:2.
[0014] Specifically, lithium carbonate accounts for the largest proportion, ensuring a sufficient supply of Li. + The source compensates for the lithium deficiency in waste LFP while avoiding excessive use that could lead to an imbalance in the lithium-iron ratio. The glucose content matches the reduction requirements of residual impurities after aerobic calcination, ensuring that insufficient dosage does not lead to incomplete reduction, while excessive dosage does not cause carbon residue that affects the electrochemical performance of the material. This solves the problem of fluctuating repair effects caused by blindly using traditional additives. Lithium dihydrogen phosphate can precisely fine-tune the lithium-phosphorus stoichiometry in the crystal, avoiding lattice distortion. The low ratio of titanium dioxide to polyethylene glycol can form a thin and uniform coating layer, which not only improves the cycle stability of the material but also avoids hindering ion conduction due to an excessively thick coating layer, thus achieving a balance between structural stability and conduction efficiency.
[0015] Preferably, the molar ratio of lithium in the lithium carbonate to iron in the precursor iron oxide is 1.032:1.
[0016] Specifically, the core reason for the performance degradation of discarded LFPs is Li + The lattice collapse caused by the absence of lithium iron phosphate (LiFe) is addressed by a lithium-iron ratio of 1.032:1, which ensures sufficient LiFe content. + It fills lattice vacancies while avoiding lattice distortion caused by excess lithium (excess Li). + (This will disrupt the olivine-type crystal structure of lithium iron phosphate); at the same time, this ratio ensures that Fe... 2+ Completely compatible with Li+ PO4 3- The combination forms a stable LiFePO4 phase, making the crystal structure of the repaired material close to that of the newly produced material.
[0017] Preferably, the solid content of the mixed slurry is 40-60%.
[0018] Specifically, a solid content of 40%-60% allows the precursor iron oxide and additives to form a uniformly dispersed slurry in pure water. This avoids the insufficient reaction contact area and low repair efficiency caused by an excessively thin slurry when the solid content is below 40%, and also solves the problems of viscous slurry, uneven stirring, and insufficient dissolution of additives when the solid content is above 60%. This ensures that reactions such as lithium replenishment and reduction occur uniformly in the slurry, improving the consistency of repair.
[0019] Preferably, in step 1, the calcination temperature is 400-600℃ and the calcination time is 3-6h.
[0020] Specifically, aerobic calcination at 400-600℃ can effectively decompose residual carbon, organic pollutants, and electrolyte residues in waste LFP black powder, while also removing some Fe. 3+ The process transforms the iron oxide into a stable precursor (Fe2O3), avoiding the problems of incomplete impurity removal at temperatures below 400℃, which affects subsequent remediation, or the agglomeration of iron oxide particles and destruction of the crystal structure at temperatures above 600℃. This ensures that the precursor iron oxide has good reactivity. The calcination time of 3-6 hours ensures that the impurities are fully oxidized and decomposed, while avoiding the defects of insufficient reaction when the time is less than 3 hours or excessive energy consumption and increased production costs when the time is longer than 6 hours. Compared with the high-temperature and long-time calcination process in traditional wet remediation, this temperature and time range can reduce calcination energy consumption, thereby saving costs.
[0021] Preferably, in step 3, the mixed slurry is milled by a sand mill, the rotation speed during the milling process is 800-2000 rpm, the milling time is 1-2 hours, and the milling medium is zirconia beads with a particle size of 0.3-0.5 mm.
[0022] Specifically, a grinding speed of 800-2000 rpm combined with a milling time of 1-2 hours can break the slurry particles to the nanoscale (typically 100-500 nm), increasing the specific surface area of the particles and improving the contact area between the composite additives and the precursor iron oxide red, thus significantly accelerating the lithium replenishment and reduction reaction rates. The 0.3-0.5 mm zirconia beads have high hardness and wear resistance, preventing debris contamination of the slurry during milling, while also allowing for precise control of particle breakage, avoiding over-milling that could damage particle crystallinity. Furthermore, nanoscale particles can shorten the Li-… +The migration path is improved, the ion conduction efficiency is enhanced, and the contact area between the electrode and the electrolyte is increased, thus improving the electrochemical reaction kinetics. This significantly improves the rate performance of the repaired material and solves the problem of slow ion conduction caused by excessively large particles in traditional repair materials.
[0023] Preferably, in step 4, the inlet air temperature of the spray dryer is 200-250℃, the outlet air temperature is 85-105℃, the atomization pressure is 0.3-0.5MPa, the atomization frequency is 300-500Hz, and the feed rate is 10-20mL / min.
[0024] Specifically, an inlet air temperature of 200-250℃ can quickly evaporate the moisture in the slurry, avoiding the powder becoming damp and clumping due to low temperatures; an outlet air temperature of 85-105℃ ensures that the powder moisture content is below 0.5%, preventing residual moisture from causing lattice defects during subsequent sintering; optimized atomization pressure and frequency enable the slurry to form uniform micron-sized spherical particles (particle size 10-50μm), resulting in good powder flowability and avoiding problems such as uneven stress and clumping during sintering caused by particles that are too large or too small.
[0025] Preferably, in step 5, the inert gas is nitrogen or argon.
[0026] Specifically, both nitrogen and argon have extremely strong chemical stability and will not react with the powder at a sintering temperature of 700-850℃, effectively isolating it from air and preventing Fe from reacting. 2+ Oxidized to Fe 3+ At the same time, it protects the coating agents such as polyethylene glycol from being oxidized and decomposed, ensuring that reduction repair and coating modification are achieved simultaneously, thus solving the problem of repair failure caused by oxidation in the traditional sintering process.
[0027] Preferably, in step 5, the sintering temperature is 700-850℃ and the sintering time is 8-12h.
[0028] Specifically, 700-850℃ is the optimal temperature range for LiFePO4 lattice repair. This temperature can activate atomic diffusion, allowing the lithium-replenished LiFePO4 to recover its crystal structure. + Fe 2+ PO4 3- The crystal structure is rearranged to form a complete olivine-type crystal structure, while promoting the formation of a uniform coating layer of titanium dioxide and polyethylene glycol. The sintering time of 8-12 hours ensures complete reaction and avoids problems such as incomplete lattice repair and weak coating layer bonding when the temperature is below 700℃, or grain growth, reduced specific surface area, and decreased electrochemical performance when the temperature is above 850℃. Attached Figure Description
[0029] The invention will now be further described with reference to the accompanying drawings.
[0030] Figure 1 This is a schematic flowchart of the lithium iron phosphate wet remediation method according to Embodiment 1 of the present invention. Detailed Implementation
[0031] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0032] The terminology used in the embodiments of this application is for the purpose of describing particular implementations only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the implementations of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0033] It should be understood that in the various embodiments of this application, the sequence number of each process does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0034] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.
[0035] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0036] Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this application can be purchased commercially or prepared using existing methods. For example, the sources and types of raw materials involved in the following examples and comparative examples are as follows: Waste lithium iron phosphate black powder: taken from retired BYD e6 electric vehicle power batteries, after disassembly and stripping of the positive electrode current collector aluminum foil, it is prepared by high-speed pulverizer with a particle size ≤10μm, lithium content 0.08mol / g, iron content 0.09mol / g, and initial specific capacity 110mAh / g. Lithium carbonate: Industrial grade, model LR-995, purity ≥99.5%, manufactured by Jiangxi Ganfeng Lithium Industry Co., Ltd., appearance is white powder, moisture ≤0.1%; Glucose: Industrial grade, model GP-01, purity ≥99.0%, manufactured by Shandong Xiwang Sugar Industry Co., Ltd., crystallinity ≥95%, moisture ≤0.5%; Lithium dihydrogen phosphate: Industrial grade, model LDP-99, purity ≥99.0%, manufactured by Changzhou Lithium Source New Energy Technology Co., Ltd., lithium content ≥16.5%, pH value (1% aqueous solution) 4.5; Titanium dioxide: Industrial grade, model TiO2-50, particle size 50nm, manufactured by Shanghai Aladdin Biochemical Technology Co., Ltd., anatase type, purity ≥99.8%; Polyethylene glycol: Industrial grade, model PEG-2000, molecular weight 1800-2200, manufactured by Jiangsu Haian Petrochemical Plant, hydroxyl value 50-60mgKOH / g, moisture ≤0.2%.
[0037] Pure water: Industrial-grade deionized water with a conductivity of ≤10μS / cm, prepared by a laboratory ultrapure water system (model UPT-II-20T, manufactured by Chengdu Ultrapure Technology Co., Ltd.). Acetylene black: conductive grade, model AB-50, manufactured by Tianjin Dolphin Carbon Co., Ltd., specific surface area ≥60m². 2 / g, oil absorption value ≥180ml / 100g; Polyvinylidene fluoride (PVDF): Battery grade, model 6020, manufactured by Shanghai Sanai Fu New Materials Co., Ltd., purity ≥99.5%, viscosity (25℃, 1% NMP solution) 2.0-3.0 Pa. s; N-Methylpyrrolidone (NMP): Battery grade, model NMP-99.9, manufactured by Jiangsu Enhua Pharmaceutical Co., Ltd., purity ≥99.9%, moisture ≤0.05%; Electrolyte (1mol / L LiPF6” / EC+DMC): Battery grade, manufactured by Shenzhen Xinzhoubang Technology Co., Ltd., EC to DMC volume ratio 1:1, moisture ≤20ppm.
[0038] Example 1 This embodiment discloses a method for wet remediation of lithium iron phosphate, including the following steps: Step 1: After passing the waste lithium iron phosphate black powder through a 200-mesh sieve to remove large particulate impurities, it is then placed in a box-type resistance furnace and calcined at 450°C for 4 hours under aerobic conditions to obtain the precursor iron red. Step 2: Weigh lithium carbonate, glucose, lithium dihydrogen phosphate, titanium dioxide, and polyethylene glycol in a mass ratio of 50:5:2:1:2 and mix them evenly to obtain a composite additive. Based on the mass of the precursor iron oxide red obtained in Step 1 (approximately 18g), take 12% of the total mass of the composite additive (i.e., 2.16g) of the precursor iron oxide red, ensuring that the molar ratio of lithium in lithium carbonate to iron in iron oxide red is 1.032:1. Then, add the composite additive and the precursor iron oxide red to a high-speed mixer containing pure water and stir at 800 rpm for 30 minutes until completely dissolved to obtain a mixed slurry with a solid content of 50%. Step 3: Transfer the mixed slurry into a horizontal sand mill, use 0.4mm zirconia beads as the medium, and mill at 1200rpm for 1.5h to obtain a nano-sized slurry with a particle size of 100-300nm. Step 4: Pass the nano-sized slurry into the spray dryer, set the inlet air temperature to 220℃, the outlet air temperature to 95℃, the atomization pressure to 0.4MPa, the atomization frequency to 400Hz, and the feed rate to 15mL / min to obtain spherical powder. Step 5: Place the powder in a tube sintering furnace, purge with nitrogen for protection, and sinter at 750°C for 10 hours to obtain the sintered material. Step 6: Crush the sintered material using an air jet mill to obtain the repaired lithium iron phosphate sample.
[0039] Example 2 Compared with Example 1, the only difference is that in step 4, the inlet air temperature is set to 200℃, the outlet air temperature to 85℃, the atomization pressure to 0.3MPa, the atomization frequency to 300Hz, and the feed rate to 10mL / min; the other steps and conditions remain the same, and the repaired lithium iron phosphate sample is finally obtained.
[0040] Example 3 Compared with Example 1, the only difference is that in step 4, the inlet air temperature is set to 250°C, the outlet air temperature to 105°C, the atomization pressure to 0.5MPa, the atomization frequency to 500Hz, and the feed rate to 20mL / min; the other steps and conditions remain the same, and the repaired lithium iron phosphate sample is finally obtained.
[0041] Example 4 Compared with Example 1, the only difference is that in step 5, the sintering temperature is 700℃ and the sintering time is 12h; the other steps and conditions remain the same, and the repaired lithium iron phosphate sample is finally obtained.
[0042] Example 5 Compared with Example 1, the only difference is that in step 5, the sintering temperature is 850°C and the sintering time is 8 hours; the other steps and conditions remain the same, and the repaired lithium iron phosphate sample is finally obtained.
[0043] Comparative Example 1 Compared with Example 1, the only difference is that in step 1, the waste lithium iron phosphate black powder is placed directly into the box-type resistance furnace without being sieved; the other steps and conditions remain the same, and finally the repaired lithium iron phosphate sample is obtained.
[0044] Comparative Example 2 Compared with Example 1, the only difference is that in step 2, all substances except lithium carbonate are removed from the composite additive, while the other steps and conditions remain the same, and the repaired lithium iron phosphate sample is finally obtained.
[0045] The performance of the repaired lithium iron phosphate obtained in Examples 1-5 and Comparative Examples 1-2 was tested. The test items and test methods are as follows: Specific capacity test: Referring to GB / T31484-2015 "Lithium-ion Battery Cathode Materials" standard, the repaired lithium iron phosphate was mixed with acetylene black and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was added to prepare a slurry. The slurry was coated on aluminum foil, vacuum dried at 120℃ for 12h, and then stamped into Φ12mm electrode sheets. Using lithium metal as the counter electrode and 1mol / L LiPF6" / EC+DMC (volume ratio 1:1) as the electrolyte, CR2032 coin cells were assembled in an argon glove box. The battery was charged and discharged at a rate of 0.1C within a voltage range of 2.0-4.2V, and the first discharge specific capacity was recorded. Cycle life test: Using the above-mentioned button cells, charge and discharge cycle tests were conducted at a 1C rate within a voltage range of 2.0-4.2V. The discharge specific capacity after 500 cycles was recorded, and the capacity retention rate was calculated as (capacity after cycle / initial capacity × 100%). Particle size: The particle size distribution of the repaired material was measured using a laser particle size analyzer, and the D50 (median particle size) was recorded. Electrochemical impedance spectroscopy: The coin cell was subjected to AC impedance testing using an electrochemical workstation, with a frequency range of 10 Hz. -2 -10 5 Hz, amplitude 5mV, record charge transfer impedance (Rct).
[0046] The test results are listed in Table 1, as follows: Table 1
[0047] Analysis of the data in Table 1 shows that the initial discharge specific capacity of Examples 1-5 all reached over 148 mAh / g, far exceeding that of Comparative Examples 1-2, and the capacity retention rate after 500 cycles all exceeded 86%, significantly better than Comparative Examples 1-2. This indicates that the process steps of the present invention can effectively repair lattice defects and supplement Li. +This improves the electrochemical performance of the material. However, Comparative Example 1, due to the lack of sieving, had residual impurities that led to uneven reaction; Comparative Example 2, lacking the reducing and coating effects of composite additives, also resulted in poor repair effects.
[0048] The median particle size D50 of Examples 1-5 is between 0.78-0.92 μm, which is much smaller than that of Comparative Examples 1-2. This is due to the nano-sizing process of the sand milling step and the granulation effect of spray drying. The small particle size can shorten the Li + Migration path, reducing charge transfer impedance.
[0049] The charge transfer impedance Rct of Examples 1-5 is all below 92Ω, which is significantly lower than that of Comparative Examples 1-2, indicating that the coating layer formed by the composite additive can reduce interfacial impedance and improve ion conduction efficiency.
[0050] In summary, this invention achieves efficient remediation of waste lithium iron phosphate through sieving pretreatment, composite additive combination, and precise process parameter control. The electrochemical performance of the remediated material is close to that of new material, and the process has low cost and low wastewater discharge, demonstrating excellent environmental friendliness.
[0051] The foregoing has described several embodiments of the present invention in detail, but these descriptions are merely preferred embodiments and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.
Claims
1. A method for wet remediation of lithium iron phosphate, characterized in that, Includes the following steps: Step 1: After sieving the waste lithium iron phosphate black powder, calcine it under aerobic conditions to obtain the precursor iron red. Step 2: Add the precursor iron oxide and composite additive to pure water and stir evenly to obtain a mixed slurry; Step 3: Mill the mixed slurry to obtain a nano-sized slurry; Step 4: Spray dry the nano-sized slurry to obtain powder; Step 5: Sinter the powder under inert gas protection to obtain sintered material; Step 6: Crush the sintered material to obtain repaired lithium iron phosphate.
2. The method for wet remediation of lithium iron phosphate according to claim 1, characterized in that, The components of the composite additive include lithium carbonate, glucose, lithium dihydrogen phosphate, titanium dioxide, and polyethylene glycol.
3. The method for wet remediation of lithium iron phosphate according to claim 2, characterized in that, The mass ratio of lithium carbonate, glucose, lithium dihydrogen phosphate, titanium dioxide, and polyethylene glycol is 50:5:2:1:
2.
4. The method for wet remediation of lithium iron phosphate according to claim 3, characterized in that, The molar ratio of lithium in the lithium carbonate to iron in the precursor iron oxide is 1.032:
1.
5. The method for wet remediation of lithium iron phosphate according to claim 1, characterized in that, The solid content of the mixed slurry is 40-60%.
6. The method for wet remediation of lithium iron phosphate according to claim 1, characterized in that, In step 1, the calcination temperature is 400-600℃ and the calcination time is 3-6h.
7. The method for wet remediation of lithium iron phosphate according to claim 1, characterized in that, In step 3, the mixed slurry is milled by a sand mill. The milling speed is 800-2000 rpm, the milling time is 1-2 hours, and the milling medium is zirconia beads with a particle size of 0.3-0.5 mm.
8. The method for wet remediation of lithium iron phosphate according to claim 1, characterized in that, In step 4, the inlet air temperature of the spray dryer is 200-250℃, the outlet air temperature is 85-105℃, the atomization pressure is 0.3-0.5MPa, the atomization frequency is 300-500Hz, and the feed rate is 10-20mL / min.
9. The method for wet remediation of lithium iron phosphate according to claim 1, characterized in that, In step 5, the inert gas is nitrogen or argon.
10. The method for wet remediation of lithium iron phosphate according to claim 1, characterized in that, In step 5, the sintering temperature is 700-850℃ and the sintering time is 8-12h.